2022
DOI: 10.3390/nu14194137
|View full text |Cite
|
Sign up to set email alerts
|

Feeding the Brain: Effect of Nutrients on Cognition, Synaptic Function, and AMPA Receptors

Abstract: In recent decades, traditional eating habits have been replaced by a more globalized diet, rich in saturated fatty acids and simple sugars. Extensive evidence shows that these dietary factors contribute to cognitive health impairment as well as increase the incidence of metabolic diseases such as obesity and diabetes. However, how these nutrients modulate synaptic function and neuroplasticity is poorly understood. We review the Western, ketogenic, and paleolithic diets for their effects on cognition and correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 221 publications
0
11
0
1
Order By: Relevance
“…The association may also be explained by the fact that such a diet reduces hypertension, a risk factor of cognitive decline, 70 a healthy eating regimen may have an impact on this risk factor. Additionally, by keeping the consumption of red or processed meat and sweets low in the DASH diet, the deleterious effect of high fat/sugar on brain inflammation and the production of amyloid beta protein may be minimized 71 . Finally, perturbation or improvement of the gut microbiome by diet may also be a pathway, 43,72,73 with support from a prior NYUWHS study that found enrichment of pro‐inflammatory gut microbes in women reporting more SCCs 43 .…”
Section: Discussionmentioning
confidence: 99%
“…The association may also be explained by the fact that such a diet reduces hypertension, a risk factor of cognitive decline, 70 a healthy eating regimen may have an impact on this risk factor. Additionally, by keeping the consumption of red or processed meat and sweets low in the DASH diet, the deleterious effect of high fat/sugar on brain inflammation and the production of amyloid beta protein may be minimized 71 . Finally, perturbation or improvement of the gut microbiome by diet may also be a pathway, 43,72,73 with support from a prior NYUWHS study that found enrichment of pro‐inflammatory gut microbes in women reporting more SCCs 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Finally, SCSFAs may have also effect on mental health through epigenetic regulation; they can inhibit histone deacetylases (HDACs) that in turn leads to increased acetylation of histones and thus changes in gene expression involved in inflammation, synaptic plasticity, and stress response, which are all implicated in the development of mental health disorders [ 58 , 59 ]. A proof that carbon length matter is that long chain saturated fatty acids (LCSFA) as palmitate was found to stimulate inflammation in macrophages and affect microglial and astrocytic signaling pathways [ 60 , 61 ]. Also, MSCSFA as lauric acid may have beneficial effects on cognition reducing the inflammation induced by LPS in microglia [ 62 ] and regulating the production of cytokines and neurotrophic factors [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…12 Además, el consumo de altas dosis de azúcar por sí mismo afecta al cerebro, dificultando las sinapsis y reduciendo la neurogénesis. 13 Los mecanismos biológicos por los que la dieta mediterránea pueden mejorar la cognición se relacionan con un aumento de antioxidantes, vitaminas y grasas no saturadas, ya que disminuyen el estrés oxidativo, la inflamación crónica y facilitan la plasticidad y andamiaje neuronal. 8 Considerando lo anterior, una dieta variada en vegetales, semillas (nueces, almendras, etc.…”
Section: Issn: 2683-1422unclassified